The effect of eight-week TRX exercises on mild and moderate posture disorders - Çakaroğlu, Deniz (Progress in Nutrition, 2020)
Study Objectives: This study was conducted to measure the effect of eight-week TRX exercises on mild and moderate posture disorders. Methods: 40 people (f: 24; m: 16), with exercise and control groups having 20 each, participated in the study. It was ensured that the exercise group performed various exercises with TRX instruments, three days a week for eight weeks. Before and after the exercise, measurements were taken from both groups with the “Scoliometer”, and only the degree of curvature, shoulder, and chest circumference measurements were taken without applying any exercise program to the control group. Statistical data were obtained using frequency and percentage values in SPSS 22; the independent sample t test was applied to compare descriptive statistics, and the repeated measures ANOVA was used, whereby the level of significance was taken as 0.001 and 0.005. Results: A statistically significant difference was found between the pre-test and post-test scores of the male exercise-control, female exercise-control, and total study groups based on the variable of shoulder, chest, and posture degree of curvature. Compared with the Bonferroni family-wise-error control method, a significant difference was found between the male exercise group participants and the control group in shoulder measurements (p <.0001), and no difference was found between female groups. In comparison of female exercise and control groups based on the chest variable, the difference was found to be significant (p <.0001), but no statistically significant difference was observed between the male exercise and control groups and a significant difference was observed between the pre-test and post-test in the degrees of curvature of women and men (exercise-control), and the pre-test predicted the post-test in the same degree of curvature and group (p <.0001). Conclusion: Besides, TRX exercises provide positive changes in the anthropometric structure and reduce posture curvature, especially those with high degrees of curvature were found to decrease significantly.